Improving the spatio-temporal characterisation of South Africa's dynamic coastal zone using hyper-temporal satellite imagery - Bessinger, Maria Magaretha Magdalena (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.